2018
DOI: 10.1159/000493005
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Rarefaction and Myocardial Fibrosis in Hypertrophic Obstructive Cardiomyopathy

Abstract: Background: Hypertrophic obstructive cardiomyopathy (HOCM) is a myocardial disease characterized by fibrosis and microvascular ischemia. Microvessels play a critical role in myocardial fibrosis in HOCM. However, it remains unclear whether or not myocardial fibrosis is associated with microvascular density (MVD) changes. Objective: The aim of the present study was to investigate whether a reduction in MVD is related to myocardial fibrosis in HOCM cardiac samples. Methods: We analyzed MVD and fibrosis in myectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…In this study, we found that the microvessel density in myocardium of cTNTQ92 transgenic mice was signi cantly lower. This observations is consistent with our previous ndings for human HCM myocardium [4]. We also found the expression levels of both CD36 mRNA and CD36 protein in the myocardium of cTNTQ92 transgenic mice were signi cantly higher than those of the control group, which suggest that CD36 expression levels may be associated with angiogenesis in HCM.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found that the microvessel density in myocardium of cTNTQ92 transgenic mice was signi cantly lower. This observations is consistent with our previous ndings for human HCM myocardium [4]. We also found the expression levels of both CD36 mRNA and CD36 protein in the myocardium of cTNTQ92 transgenic mice were signi cantly higher than those of the control group, which suggest that CD36 expression levels may be associated with angiogenesis in HCM.…”
Section: Discussionsupporting
confidence: 93%
“…Dysfunction of coronary microvasculature is also a major change in heart during HCM and myocardial fibrosis (24,25). PDGFR is widely studied in multiple pathological processes such as cancer, fibrosis, and atherosclerosis and functions through promoting cell proliferation, angiogenesis, and many other cell behaviors; therefore, it is regarded as an ideal candidate for drug development (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Microvasculature included capillaries (area 10-78.5 μm 2 , lumen diameter <10 μm) and precapillary arteries (area 78.5-314 μm 2 , lumen diameter <10-20 μm), microvessels were tagged by the pathologists on the monitor image and counted in 6 fields at ×200 magnification using Image-Pro Plus 6.0 image analysis software (Media Cybernetics Inc., Buckinghamshire, UK) to calculate microvessels. Finally, the mean number of microvessels per square millimeter was calculated and expressed as the MVD [Tian 2018].…”
Section: Surgical Techniquementioning
confidence: 99%
“…The slice was put in acid water and phosphomolybdic acid (1 min), and then aniline blue was added and washed with acid water. Six fields of view randomly were selected at ×200 magnification, and the percentage (%) of the area of fibrosis was calculated after labeling by a pathologist using Image-Pro Plus 6.0 image analysis software (Media Cybernetics Inc., Buckinghamshire, UK) [Tian 2018].…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation